Cost Utility Analysis in Pathology Laboratory Testing: Review of Literature and Proposal of New Descriptive Model for Cost Analysis (Journal of Pharmaceutical Negative Results, 2022)
In recent decades, the adoption of diagnostic laboratory techniques in clinical practice has accelerated. The cost of undertaking the care of an increasingly growing population of chronic systemic illnesses and malignancies is agonizing the health care system. A more health conscious population also demands sophisticated laboratory detection technology. From a consumer’s point of view, they want accountability for both quality and safety. Laboratories can no longer rely only on efficient testing to meet their needs. The value of laboratory tests has been determined largely by payers, and until recently, many assumed that the tests were commodities. Payers are increasingly inquiring about the tests' value, which is defined as quality per unit of expense. Laboratories must also demonstrate that their tests are also cost-effective. The incremental cost-effectiveness ratio (ICER) is a cost-effectiveness analysis statistic used to summarize the cost-effectiveness of a health care intervention. The impact of an intervention on patient mortality and morbidity is included in cost-utility analysis (CUA), a type of CEA in which the benefits of an intervention are quantified in terms of quality-adjusted life years (QALYs) gained. This article will provide an in-depth review of literature on the various cost effectiveness of oral pathology laboratory testing and a new descriptive model for assessing the quality and value of latest laboratory tests. This new proposal can be used to efficiently evaluate the effectiveness of a new laboratory protocol against the gold standard.